Jamaica : 2016 Article IV Consultation, Eleventh and Twelfth Reviews Under the Extended Fund Facility and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Jamaica. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper aims to discuss the economic reform program in Jamaica that focuses on reducing macroeconomic vulnerabilities, fostering growth, creating conditions for financial deepening and inclusion, reallocating public resources to maximize economic returns, and improving competitiveness. After three years of difficult economic reforms, inflation is at historical lows, current account deficit has more than halved, net international reserves have doubled, and access to domestic and international financial markets has been restored, supported by upgrades in credit ratings and historically high business confidence indicators. Comprehensive reforms in tax policy and administration have been and continue to be undertaken, while strict adherence to fiscal discipline have helped place debt on a downward trajectory.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet